Increasing participation as a model for the management of Islamic insurance: Parties form and means of operation and success - Abu-mounes, Raed (An-Najah University Journal for Research - B (Humanities), 2020)
This study deals with a statement the parties to form in the framework of increased participation in Islamic Insurance Company, and describes the types of claimants of the company to fulfill its obligations, as well as providing a detailed mechanism on how to manage the Islamic Insurance Company through the increasing capital participation model, which is represented through a common portfolio that combines the capital of both the shareholders and the policyholders, this model represents the Islamic Insurance Company asa capital-based company, where the policyholders have the ability to increase their shares.This model will satisfy the different needs and wants of customers of the Islamic insurance company.And in order to achieve these goals, the study illustrated themain operations of the Islamic insurance company through five offices of operation: the first office: Reception Customer Service and being decades increasingly involved with the campaign documents,SecondOffice: operations management, which are contractsfor trade-offs with service providers on one hand, and the beneficiaries of Islamic insurance in all sectors on the other hand, Third Office: Accounting Department of Interior, which manages the contracts of partnerships with service providers, The fourth Office: Management of exit and liquidation, which regulates contracts trade-offs with the beneficiaries of insurance, and the fifth Office: Management of audit and control, together with the benchmarks to help the success of the application form to participate in the growing Islamic insurance company.This study has concluded that founding the relationship between the policyholders and the Islamic insurance company on the basis of a capital-based company, where the company management is employed for the purpose ofinvesting the company assets, In exchange for a return, in a way that achieves the goals of both the Islamic insurance company and thegoals of thepolicyholders. This foundation is concluded to be the optimal Islamic module, for it achievesIslamiccredibility and economic efficiency, as well as achieving harmony between the intents of the policyholders and the shareholders in the Islamic insurance company.